Evaluation of peripheral nerve involvements in patients with familial Mediterranean fever - Atak Karabacak,; Rahşan İnan,; Nesrin Şen, (Archives of Rheumatology, 2023)
Objectives: The aim of this study was to evaluate possible peripheral and autonomic nerve involvement in familial Mediterranean fever (FMF) patients with nerve conduction studies, sympathetic skin response (SSR) and RR interval variability (RRIV). Patients and methods: The comparative case series was conducted with 76 participants between November 2017 and December 2018. Forty-six FMF patients, [12 with amyloidosis (5 males, 7 females; mean age: 44.7±13.9 years) and 34 without amyloidosis (14 males, 20 females; mean age: 35.9±8.7 years)], and 30 healthy volunteers (11 males, 19 females; mean age: 38.4±10 years) were included in this study. Nerve conduction parameters, SSR latency and amplitude from palmar and plantar responses, and RRIV at rest and deep breathing were studied in all the subjects. Neuropathic symptoms of the patient group were evaluated using the survey of autonomic symptoms scale and the neuropathy disability score. Results: Nerve conduction studies of the patient group revealed polyneuropathy in seven (15.21%) patients and carpal tunnel syndrome in six (13.04%) patients. The mean amplitudes of SSR measured from the soles were significantly lower than the control group (p=0.041). The mean values of RRIV during rest and hyperventilation were lower in the patient group compared to the control group, but no statistically significant difference was found (p=0.484, p=0.341). Conclusion: We detected that the prevalence of carpal tunnel syndrome in our patient population (13.04%) was higher than in the general population. Most of the changes in the range of parameters of SSR and RRIV determined in the patient group did not reach statistical significance, suggesting subclinical dysautonomia in FMF patients.